A Review of Risk Management in Homestays - Kiswantoro, Amin; Sugiarto, Sugiarto; Bahri, Asep Syaiful; Hendratono, Tonny; Susanto, Dwiyono Rudi; Rohman, Nur; Irawati, Novi (Jayapangus Press, 2024)
Studies on risk management in the tourism sector have been conducted, but studies on risk management, particularly for homestays, are lacking. This paper presents a theoretical study that provides an overview of the relevant theories on risk management in homestays. The literature review section presents selected articles appropriate to the research topic for review using identification, screening, eligibility, analysis, and conclusion steps. Risk management in homestays is crucial to avoid risks arising from the homestay management process itself and to create tourist satisfaction and loyalty. Novelty of this research is presents a complete explanation with data in the field, unlike previous studies that only presented articles with brief descriptions without accurate field data. The relevant theories selected in this study are also explained explicitly according to their function in the study.The purpose of this article is to identify articles that are related to the topic of risk management in homestays by grouping them into references, methods, main results, and limitations tables. Then from the selected articles, we present them in the form of a novelty table to make it easier to find novelty. Then finally, we created a special table that provides an explanation related to the variables discussed in this study. The selected data was obtained through the Scopus and Google Scholar tools which were entered into a table in CSV format. Furthermore, the database is used as a basis for conducting theoretical studies and literature reviews. This study uses a qualitative descriptive analysis method. The results of the study show that most of the articles related to the topic of risk management in homestays only present brief reviews and brief descriptions without providing explanations and understanding with accurate data research in the field. Many articles were also found that did not use basic theories that had a relationship between one variable and another.